Bone marrow lesions: etiology and pathogenesis at the hip. Issue 3 (7th December 2020) - Munsch, Maria A; Safran, Marc R; Mai, Matthew C; Vasileff, W Kelton
Abstract: Bone marrow lesions (BML) are painful changes in subchondral bone which can be reliably identified on magnetic resonance imaging and have been identified in patients suffering from hip osteoarthritis (OA) and related conditions. Created via repetitive microdamage at the articular surface and dysregulated subchondral healing, BML have been linked to traumatic, inflammatory, degenerative, metabolic and neoplastic processes. While BML are known to be a common pathology throughout the body, BML at the hip have not been extensively studied in comparison to those at the knee. Due to the hip's unique biomechanical architecture, function and loading, and independent risk factors leading to hip OA, hip BMLs must be independently understood. The identification of BML in the setting of a pre-osteoarthritic condition may provide a target for treatment and prevention of joint degeneration. By continuing to define and refine the relationships between BML, subchondral bone cysts and OA, prevention, diagnosis and treatment of OA could shift, leading to an improved quality of life and increased longevity of individuals' native hips.